Customers' Perception of Fish Fast-Casual Restaurants. Issue 3 (3rd April 2018) - Castellini, Alessandra; Samoggia, Antonella
ABSTARCT: The objective of the research is to explore Italian customers' perceptions of fish and seafood fast-casual foodservice restaurants, so to identify expected food, environmental, and organizational attributes' importance. The sample includes 600 fish and seafood customers interviewed face to face. Data elaboration included an exploratory factor analysis on fast-casual food and restaurant attributes, followed by chi-square and ANOVA to profile customers' perception towards the level of importance of the factors. Hygiene, personnel, and sensorial attributes are the three most important factors for all groups of customers. Gender and age are the most differentiating socio-economic characteristics. This study is a pioneering research on a restaurant format expanding in European countries and validated an attribute assessment scale for fast-casual restaurants. Results suggest the following managerial implications useful to define investment strategies: guaranteeing high hygiene standards, investing on personnel quality, offering tasty and good food, and targeting strategies focused on customers' lifestyle.